Washback Effects of Board-Based Speaking Tests - Sevilla Morales, Henry (2020)
This study analyzes the opinions of a group of three English as a Foreign Language programs, on the washback effects of board-based oral tests on the students’ language proficiency and foreign language anxiety levels, and on the professors’ instructional choices and decision making. With purposive sampling strategies and triangulation techniques, strong washback effects on learners’ foreign language anxiety levels and professors’ instructional choices, with lesser effects on learners’ proficiency levels and instructors’ decision making, were identied.